How private equity achieves return on investment in ophthalmology. Issue 5 (12th September 2022) - Shah, Chirag P.; Wolfe, Jeremy D.
Abstract : Purpose of review: To review how private equity entities generate profit for investors and ophthalmologists. Recent findings: There is a preponderance of private equity acquisitions and consolidation in ophthalmology. These private equity entities generate revenue by growth, profit improvement, and efficient use of capital structure. Physician partners sell their revenue and assets to a private equity entity while retaining a percentage of future profit. In general, a greater percentage going forward, will result in a smaller initial buyout. Partners typically receive payment in the form of cash and stock in the private equity entity, aligning incentives of both parties to grow and succeed. Junior associates and future partners typically do not benefit from the cash buyout but might have opportunity to buy shares in the private equity entity. Summary: The ophthalmology job market has changed significantly with the rise in private equity. Private equity investors profit from organic growth, economies of scale, and future revenue of ophthalmology practices. Ophthalmology partners benefit from often sizeable buyouts and potentially profitable shares in the private equity entity. Junior and future ophthalmologist may be less likely to succeed financially compared with their contemporaries. Some private equity entities will thrive and other may fail, particularly if they are unable to attract talented new ophthalmologists.